TOURISM PROMOTION STRATEGY, CULTURAL INTRODUCTION, AND MSME DEVELOPMENT IN THE MOTOGP EVENT AT THE MANDALIKA CIRCUIT - Zunan Setiawan; Sunday Ade Sitorus; Hayu Lusianawati; Evi Sirait; Indra Iryanto Nur Hidayat; SUNDAY ADE SITORUS (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research aims to determine tourism promotion strategies, cultural introduction, MSMEs in the MotoGP event at the Mandalika Circuit. This research is descriptive qualitative research. This research describes tourism promotion strategies, cultural introduction, MSMEs in the MotoGP event at the Mandalika circuit. The data analysis technique in this research includes data presentation, data reduction, and drawing conclusions. The results of this research show that the tourism promotion strategy in the Moto GP event at the Mandalika Circuit through the Ministry of Tourism and Creative Economy website contains dimensions of entertainment, interaction, trends and customization. In introducing culture at the MotoGP event, it shows the fact that Indonesian artists and local workers have the capacity to design and create world-class works of art directly. In promoting MSMEs at the MotoGP event, the Government provides full support for MSME craft products by providing a promotional platform for MSMEs to enliven the MotoGP event. Keywords: Tourism Promotion, Cultural, MSME, MotoGP, Mandalika